119 HEMATOLOGIC AND RENAL RECOVERY IN A PATIENT WITH LIGHT-CHAIN MULTIPLE MYELOMA AND END-STAGE RENAL DISEASE AFTER TWO CONSECUTIVE STEM CELL TRANSPLANTS. Issue 1 (1st January 2007) - D'Cunha, N.; Prabhakar, S.; Cobos, E.
Abstract : We describe here an interesting case of multiple myeloma with end-stage renal disease who responded to two consecutive stem cell transplantations. A 69-year-old white male presented in May 2000 with generalized malaise and acute renal failure Workup revealed light-chain multiple myeloma. Bone marrow examination revealed > 90% atypical plasma cells. Blood tests showed β2 -microglobulin of 35.5. Twenty-four-hour urine examination revealed kappa light chain, with total protein excretion of 2, 400 mg. Patients received four cycles of VAD (vincristine, Adriamycin, and Decadron) chemotherapy with partial response, followed by autologous peripheral blood stem cell (PBSC) transplant in October 2000. Conditioning regimen was melphalan 140 mg/m 2 . The patient was in complete remission post-transplant. Hemodialysis was continued for persistent renal failure until March 2002. Renal function improved gradually, and the patient remained in remission and free of hemodialysis. In September 2005, he had a recurrence of his renal failure and multiple myeloma. Hemodialysis was reinstituted. Bone marrow examination revealed recurrence of multiple myeloma. Twenty-four-hour urine examination revealed kappa light chain of 4, 750 mg. Patients underwent second autologous stem cell transplantation using PBSCs after conditioning with melphalan 140 mg/m 2 . Post-transplant patients had 80% reduction in urinary light chain. Dialysis was needed for 6 months post-transplant, after which the patient had recovery of renal function. Post-transplant patients were treated with the immunomodulating and antiangiogenic agent thalidomide and then with the proteosome inhibitor bortezomib because of intolerance to thalidomide. The patient is now in complete remission. To date, very few cases have been described of patients receiving stem cell transplant for multiple myeloma with end-stage renal disease. However, no case has been described in which patient received two stem cell transplants and who regained renal function, as in this case. Patients with multiple myeloma and end-stage renal disease should be treated vigorously with dialysis and high-dose chemotherapy followed by stem cell transplantation. Second transplantation needs to be considered for recurrence of disease and renal failure. This may improve the quality of life as well as prolong disease-free and overall survival.